2004
DOI: 10.1038/sj.onc.1207446
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A/Cdk2 complexes regulate activation of Cdk1 and Cdc25 phosphatases in human cells

Abstract: Mitotic entry, a critical decision point for maintaining genetic stability, is governed by the cyclin B/Cyclin dependent kinase 1 (Cdc2) complex. In Xenopus oocytes and early embryos, accumulation of cyclin B activates Cdk1, which then phosphorylates and activates the positive regulator Cdc25 in an autocatalytic feedback loop. However, cyclin B levels do not increase as some human cells approach mitosis, and the key factors regulating Cdk1 activation in human cells are unknown. We report here that reducing cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 42 publications
10
75
0
1
Order By: Relevance
“…In agreement with these reports, the present study demonstrates that inhibition of G 2 phase cyclin A/cdk2 delays the cdc25-dependent activation (Mitra and Enders, 2004;Fung et al, 2007), and nuclear translocation (Gong et al, 2007) of cyclin B/cdk1. The accumulated evidence now presents a convincing case that the regulation of the G 2 phase pool of cyclin A/cdk2 is critical for cyclin B/cdk1 activation and G 2 /M progression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with these reports, the present study demonstrates that inhibition of G 2 phase cyclin A/cdk2 delays the cdc25-dependent activation (Mitra and Enders, 2004;Fung et al, 2007), and nuclear translocation (Gong et al, 2007) of cyclin B/cdk1. The accumulated evidence now presents a convincing case that the regulation of the G 2 phase pool of cyclin A/cdk2 is critical for cyclin B/cdk1 activation and G 2 /M progression.…”
Section: Discussionsupporting
confidence: 93%
“…A number of laboratories have provided evidence that G 2 phase cyclin A/cdk2 has a critical role in the timing of entry into mitosis (Furuno et al, 1999;Goldstone et al, 2001;Hu et al, 2001;Mitra and Enders, 2004;Fung et al, 2007;Gong et al, 2007), which is confirmed by our siRNA and cdk2-specific inhibitor studies. In agreement with these reports, the present study demonstrates that inhibition of G 2 phase cyclin A/cdk2 delays the cdc25-dependent activation (Mitra and Enders, 2004;Fung et al, 2007), and nuclear translocation (Gong et al, 2007) of cyclin B/cdk1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, while neither cyclin E1 nor E2 is essential for cell cycle progression during mouse development Parisi et al 2003; see below), cyclin A2 disruption results in early embryonic lethality (Murphy et al 1997). In S phase, cyclin A-Cdk2 is thought to phosphorylate substrates that start DNA replication from preassembled replication initiation complexes (Krude et al 1997;Hua and Newport 1998;Coverley et al 2002) and to be required for coordinating the end of S phase with activation of the mitotic Cdks (Mitra and Enders 2004). Because it appears to orchestrate the numerous activities required for S-phase entry, S-phase progression, and entry into mitosis, Cdk2, in particular, has been viewed as a master regulator whose activities were thought to be essential.…”
Section: G1 Regulation In Mammalian Cellsmentioning
confidence: 99%
“…The human phosphatase Cdc25A is an oncogenic protein (Galaktionov et al, 1995). Both Cdc25a and b genes are involved in tumor growth and play critical roles in regulating apoptosis and cell cycle progression (Mitra and Enders, 2004;Brezak et al, 2005). Increased expression of Cdc25A, B and C in active dephosphorylated forms are observed in aggressive human cancers (Kallstrom et al, 2005).…”
Section: Tff1 Transforming Functions and Cdc25 Phosphatases S Rodrigumentioning
confidence: 99%